Web applications with microsoft visual interdev 6.0 MCSD Training kit for exam 70-152 - Microsoft (New Delhi Prentice Hall of India, 2000)
Real-world developer training for results on the job and exam create dynamic, data driven from web applications using the visual InterDev 6.0. Web development system and official developer training-direct from Microsoft.
Keywords: Web sites; Web servers